FAKTOR-FAKTOR PENYEBAB TERJADINYA PENINGKATAN PERDAGANGAN PEREMPUAN NIGERIA KE ITALIA - Tri Nofi Astuti; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research explains the factors that caused increase women trafficking in Nigeria. Nigeria ranks Tier 2 in Watch List. Nigeria known as a transit, destination and origin country of human trafficking. In the last decade thousands of Nigerian women and girls have been trafficked into sex industry mainly to Europe. Italy is one of the countries where many Nigerian women and girls are trafficked. This research uses Constructivism perspective in International Relations. This research is also supported by Criminal Model and Human Rights Model theories and human trafficking concept. While level analysis used is society. Fact, data, arguments, and theoretical framework of this research formulate by using qualitative description. This research intended to show the factors that caused increase women trafficking in Nigeria. It is known that Nigerian women’s trafficking according to NAPTIP and IOM reports has increased significantly. Particularly from Edo state, with Italy as its main destination. The factors that caused increase women trafficking in Nigeria in this research divided into two types, internal and external. The internal factor is poverty, lack of education and knowledge, corruption, social and cultural circumstances and the practice of voodoo/Juju. While external factors are market demand and involvement of criminal networks. Keywords : Women Trafficking, Increase, Factor, Nigeria